Financing Risk Management in the Micro Business Unit of Bank Syariah Indonesia: A Case Study of the Parepare Branch - I Nyoman Budiono; Syahriayah Semaun; Andi Kiki Patmawati; Sri Sugiarti Salim; Nur Aisah Sari (Jurnal Ar-Ribh, 2026)
Risk Management is a structured and systematic process of identifying, measuring, monitoring, controlling, and communicating risks in Islamic banks. This study, entitled "Financing Risk Management in the Micro Business Unit of Bank Syariah Indonesia, Parepare Branch", aims to analyze the financing process and implementation of risk management within BSI's micro business segment in Parepare. The research employed a Descriptive Qualitative method with a case study approach. Primary data was gathered through in-depth interviews with BSI employees responsible for the Micro Business Unit in the Parepare Branch, supplemented by comparison data from BSI employees outside the region. This qualitative approach ensured a deeper understanding of financing distribution procedures and specific risk strategies.The findings reveal two main results. First, the micro financing process at BSI Parepare is comprehensive, involving customer application, SLIK Checking, field checks, thorough 5C analysis, committee approval, legal binding, disbursement, and rigorous monitoring. Second, risk management is continuous, focusing on identification, measurement, monitoring, and control. Control mechanisms emphasize the analysis of micro debtors’ character and capacity, utilizing early warning systems, and offering financing restructuring to effectively minimize potential default risks.